2023
DOI: 10.3390/medicina59101814
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Potential of Petroselinum crispum (Mill.) Fuss. on Paracetamol-Induced Hepatio-Renal Toxicity and Antiproteinuric Effect: A Biochemical, Hematological, and Histopathological Study

Ghizlane Nouioura,
Tayeb Kettani,
Meryem Tourabi
et al.

Abstract: Background and Objectives: Paracetamol overdose is a significant global issue due to its widespread use, which can lead to a lack of awareness regarding its potential side effects. Paracetamol can harm the liver, possibly resulting in liver failure. Conversely, this study employed extracts from Petroselinum crispum (PC), known for its rich content of bioactive compounds, with demonstrated antioxidant properties shown in previous research as well as protective effects against various diseases. The primary objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…This genuine variety is characterized by the synthesis of numerous hydroxycoumarins, including ferulenol 9 . Recent studies highlight the potential of isolated compounds from this genus as chemopreventive agents and in overcoming resistance to anticancer drugs 8 , 10 . Traditionally, plants of this genus have been used to treat various diseases 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This genuine variety is characterized by the synthesis of numerous hydroxycoumarins, including ferulenol 9 . Recent studies highlight the potential of isolated compounds from this genus as chemopreventive agents and in overcoming resistance to anticancer drugs 8 , 10 . Traditionally, plants of this genus have been used to treat various diseases 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In the Middle Atlas, unexpanded inflorescences of Ferula serve as anthelmintics 9 . Polyphenols have well-defined antioxidant properties linked to the inhibition of food oxidation 10 . In addition, these antioxidants effectively block or inhibit the formation and propagation of free radicals 13 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the extract significantly reduces ALT, AST, ALP, and LDH levels in the liver, which are increased by paracetamol. In addition, histopathological examinations revealed less congestion and mononuclear cell infiltration in the liver tissue [76].…”
Section: Antihepatotoxic Activitymentioning
confidence: 87%
“…It was determined that the increase in blood urea, creatinine, and triglyceride levels was inhibited by the extract. It was observed that the extract reduced urinary protein excretion compared to control groups and increased urinary creatinine and urea excretion compared to paracetamol control groups [76].…”
Section: Antinephrotoxic Activitymentioning
confidence: 89%
“…f., and Petroselinum hortense Hoffm. This plant holds significance in the food, cosmetic, and pharmaceutical industries due to its aromatic, culinary, and medicinal properties [ 7 ].…”
Section: Introductionmentioning
confidence: 99%